Hazardous Processes and Their Risk Mitigation Techniques in Iron and Steel Industry Emission in CFB Boiler- A Review - Y. Rameshkumar; R. Kandasamy; G. Murgan; G. Selvaraj (Journal of Advanced Mechanical Sciences, 2023)
Steel manufacturing industries are one of the major industries in the world where number of hazards are being involved in Daily work practices. While working in such steel industries safe operating/work procedures are too much significant as employees are exposed to various threats due to nature of job and work operations. For any industry labour is considered as a great asset which follows the work as trades. As per the New Occupational Safety and Health CODE – Hazardous Process is mentioned in two ways (i) consequence in toxic waste of universal atmosphere or (ii) reason material injury to health of a worker occupied [1]. The working environment in steel industry is too much noisy with excessive heat. In today’s world most of the steel industries are using new technologies where control systems are used in various steel manufacturing industries to control number of incidents and accidents and have precise control over steel composition addition which reflects the quality. As the safety is being considered paramount in today’s working environment, so regardless the hazardous process of various steel manufacturing industries achieving an accident free environment is achievable. Several Risk Assessment Techniques like Hazard Identification and Risk Assessment (HIRA) Techniques/Job Safety Analysis are used to reduce the work place injuries i.e. Frequency rate, severity rate and incident rate statistically and statistics of several years has been studied on the various mentioned process and injuries resulting in ill-health is mitigated [2].